PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN RETURN ON EQUITY TERHADAP PRICE TO BOOK VALUE PADA PT SEKAR LAUT TBK PERIODE 2014-2023 - Novi Misna Yanti; Dede Hendra (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the Current Ratio, Debt to Equity Ratio, and Return on Equity on Price to Book Value at PT Sekar Laut Tbk for the 2014–2023 period. The research uses quantitative methods. The population used is the financial position report and profit and loss financial report. The type of sample used is purposive sampling, namely the financial position report and profit and loss financial report for the period 2014–2023. Data analysis techniques include descriptive tests, classical assumption tests, multiple linear regression, correlation coefficients, t tests, f tests and coefficient of determination tests. All statistical tests use statistical product and service solution version 20. The research results show that partially, the Current Ratio has an effect on Price to Book Value with a tcount of 3.418 > ttable 2.447 and a significance of 0.009 < 0.05. Debt to Equity Ratio and Return on Equity have no effect with tcount values of -1.789 and -0.167 respectively, smaller than ttable. Simultaneously, the three variables influence Price to Book Value (Fcount 12.493 > Ftable 4.7374; sig. 0.005 < 0.05). The correlation coefficient (R2) of 0.862 indicates a very strong relationship, while the adjusted R² of 0.793 indicates that 79.3% of the variation in Price to Book Value is obtained by independent variables, and the remaining 20.7% is influenced by other variables not examined in this research.